Pengaruh Kualitas Layanan dan Kompetensi Guru terhadap Kepuasan Peserta Didik dengan Motivasi Belajar sebagai Variabel Intervening - Iswatun Hasanah; I Dewa Ketut Kerta Widana; Sri Yanthy Yosepha (Ameena Journal, 2026)
This study examines the effect of service quality and teacher competence on student satisfaction with learning motivation as an intervening variable at MTs Negeri 29 Jakarta. The background highlights inconsistencies in educational services and teacher competence that potentially affect student satisfaction. This research aims to analyze the direct and indirect effects among these variables. A quantitative method with a survey approach was employed, involving 100 respondents selected through simple random sampling. Data were collected using Likert-scale questionnaires and analyzed using path analysis with SPSS. The findings indicate that service quality and teacher competence have a significant direct effect on learning motivation, service quality and teacher competence have a significant direct effect on student satisfaction, and learning motivation has a significant direct effect on student satisfaction. Furthermore, learning motivation significantly mediates the effect of service quality and teacher competence on student satisfaction. The implications suggest that improving service quality and teacher competence can enhance learning motivation, which in turn increases student satisfaction. This study contributes to educational management literature by validating the mediating role of learning motivation in the context of Islamic junior high schools.